Efficient furan-bridged dibenzofulvene-triphenylamine hole transporting materials for perovskite solar cells - Wu, Nan; Zhang, Xianfu; Liu, Xuepeng; Wang, Ying; Han, Mingyuan; Ghadari, Rahim; Wu, Yahan; Ding, Yong; Cai, Molang; Dai, Songyuan (Materials advances, 2023)
Inspired by the superior properties of dibenzofulvene-triphenylamine hole transporting materials (HTMs), a rationally designed type of HTM with furan as the side-arm bridge has been synthesized, namely, FF-OMeTPA. A dibenzofulvene-triphenylamine HTM with thiophene as the side-arm bridge (FT-OMeTPA) is also prepared. The effect of heteroatomic sulfur-to-oxygen change on the molecular and photovoltaic properties in perovskite solar cells was investigated. The experimental and theoretical results illustrate that the furan-based molecule has better conjugation than the thiophene-based one, leading to higher hole mobility. The PSC employing oxygen-containing FF-OMeTPA delivered a power conversion efficiency (PCE) of 21.82%, whereas the FT-OMeTPA-based PSC exhibited a lower PCE of 18.01%. Significantly, the FF-OMeTPA-based devices also outperform those employing conventional spiro-OMeTAD. In addition, the studied molecules exhibit comparable device stability and much lower synthesis cost than spiro-OMeTAD. The perovskite solar cells employing cost-effective FF-OMeTPA exhibit a PCE of 21.82%, which is higher than the PCE of solar cells employing conventional spiro-OMeTAD.